Carcinoma of the oesophagus associated with membrano-proliferative glomerulonephritis. - Walker, J. F. (BMJ Group, 1981)
Nephrotic syndrome has been observed in association with different types of neoplasia. This appears to be the first report of the occurrence of the nephrotic syndrome due to membrano proliferative glomerulonephritis in association with carcinoma of the oesophagus. Although proteinuria was present before excision of the tumour, the nephrotic phase occurred subsequently. Eventually it disappeared leaving the patient with a clear urine and biochemical and histological improvement of the renal lesion (including immunofluorescent and electronmicroscopy studies). Possible mechanisms responsible for the nephrotic syndrome in this case are discussed.